(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Lexical causal derivation is related to the process of word formation, in which the aspects of the verbs related to the meaning of motivation and the issue of the connection of these meanings with the concept of cause are analyzed. Word formation is considered an object of examination of microsyntax and relies on the law of lexical derivation. Word formation is studied on the basis of the principles of syntactic derivation, and the formation of a derivative structure on the basis of a certain base structure is interpreted based on the operand+operator+ derivative scheme. The existing model serves as a general criterion for all types of derivation.